Integration of Integrated Marketing Communications and SEO Optimization in Skincare Product Marketing Through Influencers - Janeska Widia; Blangi Intan Maharani; Regina Marintan Silalahi; Ervina Rosarina Hasibuan; Ayu Sarlina Pasaribu; Ade Rasinta Herli Kristiani Purba (LP2M IAIN Palopo, 2026)
The development of digital technology has significantly transformed marketing communication patterns, particularly in the increasingly competitive skincare industry. Companies no longer rely solely on conventional promotion but utilize various digital marketing strategies such as Integrated Marketing Communications (IMC), Search Engine Optimization (SEO), and influencer marketing. This study aims to analyze the influence of integrated marketing communications and SEO optimization on skincare product marketing through influencers. This research employs a quantitative approach using a descriptive research method. Data were collected through questionnaires distributed online to 150 respondents who had previously searched for information or purchased skincare products through digital platforms. Data analysis techniques included descriptive statistical analysis and multiple linear regression using SPSS software. The results indicate that integrated marketing communications and SEO optimization have a positive and significant influence on skincare product marketing through influencers, both partially and simultaneously. Integrated marketing communications play a role in creating consistency in marketing messages across various digital platforms, while SEO optimization facilitates consumers in finding product information through search engines. The coefficient of determination shows that these two variables explain 46.1% of the variation in skincare product marketing through influencers. These findings indicate that synergy between integrated marketing communications, SEO, and influencer marketing can enhance product visibility, strengthen consumer trust, and increase consumer purchase intention toward skincare products in the era of digital marketing